(untitled) (Research, Society and Development, 2020)
Among the many functions that a building material needs to have, its insulation functions stand out. This type of materials acts by decreasing the conduction of heat/sound in to the environment. In this context, bio-insulations have been receiving an increasing attention due to its performance and the use of sustainable/naturals insulation materials. This study was conducted to evaluate the thermal and acoustic performance of bio-based boards made from the biomass of Spirulina, bacterial poly-β-hydroxybutyrate (PHB), and glass wool. The boards were manufactured under heated compression in different proportions: 33.33% glass wool, 33.33% PHB, and 33.33% Spirulina biomass (Board A); 20% glass wool, 40% PHB, and 40% Spirulina (Board B); 40% glass wool, 40% PHB, and 20% Spirulina (Board C); and 40% glass wool, 20% PHB, and 40% Spirulina (Board D). Boards A and B showed lower thermal conductivity (0.09 W m-1 K-1) compared to traditional insulating materials, such as gypsum neat (0.44 W m-1 K-1) and Kaolin insulating firebrick (0.08–0.19 W m-1 K-1). Board D showed the highest sound absorption coefficient of 1600 Hz compared to other bio-based insulators at the same frequency, such as polypropylene based non-woven fiber and tea-leaf-fiber with the same thickness. For the noise reduction coefficient, board B showed better results than concrete. Thus, boards A and B are suitable as thermal insulators, while boards B and D are suitable as sound insulators. For simultaneous application as a thermal and sound insulator, board B is the best choice among all boards.